2014 ASEE International Forum Proceedings
DOI: 10.18260/1-2--17203
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media to Create a Global Community of Sustainability-Engaged Students

Abstract: Florida. Matthew worked for several years in the water and sanitation sector in Honduras, including one year with a Fulbright Fellowship. He currently studies pathogen removal in wastewater treatment ponds and microbial risk in wastewater irrigation systems in Bolivia. Ms. Colleen Claire NaughtonColleen Naughton is a doctoral student at the University of South Florida in the Department of Civil and Environmental Engineering. She is advised by Dr. James R. Mihelcic. Colleen was part of the Peace Corps Master's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In general, the research experience had either a positive or a neutral impact on students' self-reported research self-efficacy, teamwork, identity, sense of belonging, cultural competency, and attitudes toward interdisciplinary research, sustainable development, and career intentions. This finding is consistent with previous studies (Casad et al 2018;Manser et al 2015;Verbyla et al 2023), which have shown the positive impact of international research experiences on student outcomes. Moreover, the results indicate that students achieved a confident level of comfort with the Brazilian culture before the summer research experience through the language and culture workshops that were provided pre-departure.…”
Section: Findings From Surveyssupporting
confidence: 93%
See 2 more Smart Citations
“…In general, the research experience had either a positive or a neutral impact on students' self-reported research self-efficacy, teamwork, identity, sense of belonging, cultural competency, and attitudes toward interdisciplinary research, sustainable development, and career intentions. This finding is consistent with previous studies (Casad et al 2018;Manser et al 2015;Verbyla et al 2023), which have shown the positive impact of international research experiences on student outcomes. Moreover, the results indicate that students achieved a confident level of comfort with the Brazilian culture before the summer research experience through the language and culture workshops that were provided pre-departure.…”
Section: Findings From Surveyssupporting
confidence: 93%
“…The involvement of community members in environmental engineering and science research using thecommunity-based participatory research (CBPR) is one way to help address environmental and social justice disparities (Montoya et al 2021). Moreover, interactions with community members may also enhance the experience of the student participants (Verbyla et al 2023) by providing new lenses when elucidating social issues or when selecting approaches to mitigate challenges. This research project allowed that fiveof the student participants to experience deep and extensive interactions with members of low-income urban favela communities.…”
Section: Research Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Among the areas where social media might be used to support and bolster cross-cultural interpersonal competence are the endeavors where it matters most; specifically in organizational communication, collaboration, recruitment, projects, relationship maintenance, transactions, and sharing. Through social networking, the people of an organization are often connected with many peers in far-flung places (Verbyla et al, 2014).…”
Section: Introductionmentioning
confidence: 99%